Using Regression Analysis to Analyze Consumption Effects from an Elementary School Vegetable Snack Program - Bodnar, Josh; Chmielowska, Isabel; Fogarty, Jared; Martell, Kjirstin; Park, Shinhoo; Pergolski, Matthew; Scheller, Selena; Soborowicz, Levi; Jamelske, Eric M. (My University, 2018)
This poster builds on the previous two posters using the same data to further investigate factors that influence children’s consumption of free vegetables served in school for afternoon snack. We present histograms of the consumption distributions for a more detailed look behind the means and standard deviations. We also use a series of regression analysis models to examine if the condition effects shown in graphical/statistical comparisons are robust to the inclusion of control variables. These analyses are limited to serving 1 and servings 2-6 for each vegetable respectively.
Color poster with text, charts, tables and graphs.
Keywords: Vegetables; Nutrition; Schoolchildren; Posters